2006
DOI: 10.1172/jci25227
|View full text |Cite
|
Sign up to set email alerts
|

Signals for stress erythropoiesis are integrated via an erythropoietin receptor-phosphotyrosine-343-Stat5 axis

Abstract: Anemia due to chronic disease or chemotherapy often is ameliorated by erythropoietin (Epo). Present studies reveal that, unlike steady-state erythropoiesis, erythropoiesis during anemia depends sharply on an Epo receptor-phosphotyrosine-343-Stat5 signaling axis. In mice expressing a phosphotyrosine-null (PY-null) Epo receptor allele (EpoR-HM), severe and persistent anemia was induced by hemolysis or 5-fluorouracil. In shortterm transplantation experiments, donor EpoR-HM bone marrow cells also failed to efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 52 publications
1
123
2
1
Order By: Relevance
“…30 It has also been reported that OSM is expressed in murine erythroblasts and supports survival of erythroid progenitors in mice under anemic conditions. 47 In the present study, however, we did not detect expression of OSM in erythroid progenitors in human bone marrow. This finding was somewhat unexpected, but fits with the observation that human erythroid progenitors also did not express phosphorylated STAT5.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…30 It has also been reported that OSM is expressed in murine erythroblasts and supports survival of erythroid progenitors in mice under anemic conditions. 47 In the present study, however, we did not detect expression of OSM in erythroid progenitors in human bone marrow. This finding was somewhat unexpected, but fits with the observation that human erythroid progenitors also did not express phosphorylated STAT5.…”
Section: Discussioncontrasting
confidence: 82%
“…The most likely explanation for this discrepancy is that phosphorylated STAT5 and OSM are not expressed in steady-state hematopoiesis but only under anemic conditions, as has been reported for phenylhydrazine-induced anemia in mice. 47 The majority of patients with systemic mastocytosis harbor the KIT mutation D816V. In this study, we found that a KIT D816V Ϫ clone of the HMC-1 cell line displayed significantly lower OSM expression levels than KIT D816V ϩ HMC-1 cells.…”
Section: Discussionmentioning
confidence: 55%
“…Associated with these transcription pathways are the mitogen-activated protein kinases, which include the extracellular signal-related kinases (ERKs), the c-Jun-amino terminal kinases, and p38 MAP kinase, which can oversee erythroid proliferation and differentiation (Nagata et al, 1998). Yet, in regard to cytoprotection, EPO has been shown to not only activate STAT 3 (Asaumi et al, 2007;Parsa et al, 2003), STAT 5 Menon et al, 2006b;Moon et al, 2006;Um and Lodish, 2006;Wei et al, 2006), and ERK 1/2 (Bullard et al, 2005;Menon et al, 2006a), but also to employ these pathways for cell development and cell protection (Figure 2). For example, EPO significantly activates STAT3, STAT5, and ERK 1/2 in primary cerebral vascular cells, suggesting that EPO may require these cellular pathways to confer EC cytoprotection during oxidative stress (Table 2).…”
Section: Epo and Jak2 Stats Erks Caspasesmentioning
confidence: 99%
“…However, in regards to cytoprotection, EPO has been shown to not only activate STAT 3 (Asaumi, et al, 2007, Parsa, et al, 2003, STAT 5 (Chong and Maiese, 2007a, Menon, et al, 2006b, Moon, et al, 2006, Um and Lodish, 2006, Wei, et al, 2006, and ERK 1/2 (Bullard, et al, 2005, Menon, et al, 2006a, but also to employ these pathways for cell development and cell protection. EPO activates STAT3, STAT5, and ERK 1/2 in primary cerebral vascular cells, suggesting that EPO may require these cellular pathways to confer EC cytoprotection during oxidative stress .…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%